Detection of Dengue Virus From Aedes aegypti (Diptera, Culicidae) in Field-Caught Samples From Makkah Al-Mokarramah, Kingdom of Saudi Arabia, Using RT-PCR - Ali, Elfadol Obeid Mohamed; Babalghith, Ahmed Omer; Bahathig, Adil Omer Saeed; Dafalla, Ommer Mohamedelhassan; Al-Maghamsi, Ibrahim Wasal; Mustafa, Nasr Eldien Ali Gaafar; AL-Zahrani, Abdullah Ahmad Abdullah; Al-Mahmoudi, Sameer Mohammed Yousef; Abdel-Latif, Mohamed E. (Frontiers in Public Health, 2022)
Dengue fever (DF) is endemic to Makkah and Jeddah, the Kingdom of Saudi Arabia (KSA). However, until recently, the circulation of dengue virus (DENV) in Aedes mosquitoes in these areas was unknown. Serological surveillance of DENV in Ae aegypti is a powerful tool for early detection of dengue outbreaks and essential for developing effective control strategies. Therefore, this research aimed to examine a sample of adult Ae aegypti mosquitoes from Makkah, KSA, to detect DENV. In total, 1295 Ae aegypti mosquitoes were collected from the field from target areas of Makkah with a high incidence and prevalence of DF. The samples were divided into 259 coded pools (five mosquitoes in each) and preserved in 1.5 mL plastic tubes. The tubes were labeled, capped, and stored at−86°C until use. RT-PCR was used to detect DENV in the samples. All positive pools were confirmed by RT-PCR. The RT-PCR products were analyzed by gel electrophoresis (1.5% agarose in Tris-acetate EDTA buffer), stained with ethidium bromide, and visualized. DENV was isolated from six female Ae Aegypti collected from six pools (out of 259 pools). No other viruses were detected. Only five of the nine target localities had positive pools. Samples from the remaining four localities yielded negative results. Four DENV-positive mosquitoes were collected at the aquatic stages, and two were collected at the adult stage. These results show the circulation of DENV in adult mosquitoes and offspring, indicating vertical transmission of DENV. In conclusion, this study found that, in Makkah, DENV is circulating in dengue vectors with a high significance rate, suggesting the possibility of a dengue outbreak in the future; therefore, a sensitive surveillance system is vital to predict the outbreak and for early intervention and control.